2019
DOI: 10.1007/s10877-019-00330-y
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of non-invasive cardiac output monitoring by electrical cardiometry: a systematic review and meta-analysis

Abstract: Cardiac output monitoring is used in critically ill and high-risk surgical patients. Intermittent pulmonary artery thermodilution and transpulmonary thermodilution, considered the gold standard, are invasive and linked to complications. Therefore, many non-invasive cardiac output devices have been developed and studied. One of those is electrical cardiometry. The results of validation studies are conflicting, which emphasize the need for definitive validation of accuracy and precision. We performed a database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 93 publications
(208 reference statements)
4
50
0
Order By: Relevance
“…A recent review of the electrical velocimetry method mentioned that this method was unable to demonstrate high accuracy when measuring the CO ( 21 ); however, it was useful for monitoring trends in the CO, as in our case. According to comparisons made among the other non-invasive methods, including echocardiography and MRI in this case, the echocardiography method tended to underestimate the CO/CI, as the calculation assumes a perfect circle for the left ventricular outflow instead of the actual elliptical shape.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A recent review of the electrical velocimetry method mentioned that this method was unable to demonstrate high accuracy when measuring the CO ( 21 ); however, it was useful for monitoring trends in the CO, as in our case. According to comparisons made among the other non-invasive methods, including echocardiography and MRI in this case, the echocardiography method tended to underestimate the CO/CI, as the calculation assumes a perfect circle for the left ventricular outflow instead of the actual elliptical shape.…”
Section: Discussionmentioning
confidence: 73%
“…2). All methods of non-invasively measuring the CO require further improvements in order to acquire high precision (3,21) (Table). Clinical research on the correlation among CO values measured by different methods is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent published review and meta‐analysis on accuracy and precision of non‐invasive cardiac output monitoring by electrical cardiometry, Sanders M et al demonstrate low bias for both adults and pediatrics, but the mean percentage error was not clinically acceptable. They concluded that electrical cardiometry cannot replace thermodilution and transthoracic echocardiography for the measurement of absolute cardiac output values, but that electrical cardiometry might still be applicable as a trend monitor to measure acute changes in cardiac output, which is relevant for clinical decision‐making 26 …”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis including a subgroup analysis of 11 pediatric studies, comparing cardiac output values derived from electrovelocimetry and transthoracic echocardiography (n = 9) and thermodilution (n = 2), found a random effects pooled bias of −0.02 L/min [95% CI −0.09 to 0.05 L/min], a limit of agreement of −1.22 to 1.18 L/min, and a mean percentage (MPE) error of 42.0%. Considering a pooled MPE of <30% as acceptable, the authors concluded that despite a low bias electrovelocimetry is unlikely to completely replace echocardiography or thermodilution, but seems to be applicable as a trend monitor capable of measuring acute changes in cardiac output in both children and adults 14 …”
Section: Methodsmentioning
confidence: 99%